Effect of Proinflammatory Cytokines on the Interplay between Roxithromycin, HMR 3647, or HMR 3004 and Human Polymorphonuclear Neutrophils - Vazifeh, D. (American Society for Microbiology, 2000)
Cytokines, the hallmarks of infectious and inflammatory diseases, modify phagocyte activities and thus may interfere with the immunomodulating properties of antibacterial agents. We have investigated whether various proinflammatory cytokines (interleukin 1 [IL-1], IL-6, IL-8, gamma interferon, tumor necrosis factor alpha [TNF-α], and granulocyte-macrophage colony-stimulating factor [GM-CSF]) modify two macrolide properties, i.e., inhibition of oxidant production by polymorphonuclear neutrophils (PMN) and cellular uptake. Roxithromycin and two ketolides, HMR 3647 and HMR 3004, were chosen as the test agents. TNF-α and GM-CSF (but not the other cytokines) decreased the inhibitory effect of HMR 3647 only on oxidant production by PMN. Fifty percent inhibitory concentrations were, however, in the same range in control and cytokine-treated cells (about 60 to 70 μg/ml), suggesting that HMR 3647 acts downstream of the priming effect of cytokines. In contrast, the impairment of oxidant production by roxithromycin and HMR 3004 was unchanged (or increased) in cytokine-treated cells. This result suggests that HMR 3004 (the strongest inhibitory drug, likely owing to its quinoline side chain) and roxithromycin act on a cellular target upstream of cytokine action. In addition, TNF-α and GM-CSF significantly (albeit moderately) impaired (by about 20%) the uptake of the three molecules by PMN. The inhibitory effect of these two cytokines seems to be related to activation of the p38 mitogen-activated protein kinase. Our data also illuminate the mechanism underlying macrolide uptake: protein kinase A- and tyrosine kinase-dependent phosphorylation seems to be necessary for optimal uptake, while protein kinase C activation impairs it. The relevance of our data to the clinical setting requires further investigations, owing to the complexity of the cytokine cascade during infection and inflammation.